Reclaiming physician identity: It’s time to integrate ‘Doctor as Person’ into the CanMEDS framework - Dagnone, Jeffery Damon; Glover Takahashi , Susan; Whitehead, Cynthia; Spadafora, Salvatore (Revue canadienne de l’éducation médicale, 2020)
In 1996, the Royal College of Physicians & Surgeons of Canada (RCPSC) adopted the CanMEDS framework with seven key roles: medical expert, communicator, collaborator, health advocate, manager, professional, and scholar. For many years, CanMEDS has been recognized around the world for defining what patients need from their physicians. From the start, the RCPSC acknowledged that these roles should evolve over time to continue to meet patient and societal needs (updates in 2005 & 2015). We propose that an 8th role is now needed in the framework: “Doctor as Person”. Interestingly, this role was present in the foundational work through the Educating Future Physicians for Ontario (EFPO) project that the RCPSC drew upon in creating CanMEDS more than 20 years ago. Given today’s challenges of providing care in an increasingly stressed Canadian healthcare system, physicians are struggling more than ever with health and wellness, burnout, and the deterioration of the clinical environment. From the patient perspective, there is growing concern that physician-patient interactions are becoming increasingly impersonal and decreasingly patient-centered. The crack emerging in the foundation of physician identity needs to be remedied. We need to pay close attention to how we define ourselves as physicians, by better identifying the competencies required to navigate the personal and professional challenges we face. Only in so doing can we ward off the threat that exists in losing authentic human to human care interactions. Formalizing Doctor as Person as an 8th role in the CanMEDS framework will help patients and physicians create the space to have essential conversations about the humanity of medical care.